Influence of F– Ions as Flux from Different Resources on Vitrified Bond for Cubic Boron Nitride Grinding Tools - Ye, Hang; Li, Zhihong; Zhu, Yumei; Shan, Dongdong (Asian Journal of Chemistry, 2011)
In this article, the selection of more appropriate flux applied to Na2O-B2O3-Al2O3-SiO2 bonding glass for cubic boron nitride grinding tools was studied. The bending strength of the specimens was tested by three-point bending strength tester and microstructure characteristics of specimens were observed by scanning electron microscopy. Thermal expansion coefficient of bonding glass was tested by high-temperature dilatometer. The results presented that the type of flux had a great effect on the performance of vitrified bond grinding specimens. The refractoriness, fluidity and wettability were improved with the introdution of F– ions no matter in the form of Na3AlF6 or CaF2. Better properties of vitrified bond, such as refractoriness, fluidity and wettability, could be obtained when F– ions was introduced in the form of Na3AlF6, however, the mechanical properties of specimens was better when CaF2 was introduced owing to the feasible expansion value of bonding glass with CaF2. Therefore, the selection of appropriate resource of F– was determined by various properties of vitrified bond.